Residential Integration on the New Frontier: Immigrant Segregation in Established and New Destinations - Hall, Matthew (2013)
This article explores patterns and determinants of immigrant segregation for 10 immigrant groups in established, new, and minor destination areas. Using a group-specific typology of metropolitan destinations, this study finds that without controls for immigrant-group and metropolitan-level characteristics, immigrants in new destinations are more segregated and immigrants in minor destinations considerably more segregated than their counterparts in established destinations. Neither controls for immigrant-group acculturation or socioeconomic status nor those for demographic, housing, and economic features of metropolitan areas can fully account for the heightened levels of segregation observed in new and minor destinations. Overall, the results offer support for arguments that a diverse set of immigrant groups face challenges to residential incorporation in the new areas of settlement.